Penggunaan Asas Beban Pembuktian Terbalik sebagai Penyelesaian Perkara Kesalahan yang Dilakukan Oleh Dokter - Randika Fitrah Darmawan; Slamet Sampurno Soewondo; Sabir Alwi (Faculty of Law, Universitas Pattimura, 2021)
This study aims to identify and analyze criminal procedural law arrangements in resolving cases of wrongdoing committed by doctors; and legal protection for patients in reverse proof of the settlement of wrongdoing by doctors. The research method used is normative juridical research, the type of research is descriptive analytical. The source of legal materials is primary and secondary legal materials. The technique of collecting legal materials is carried out by library research on legal materials, both primary legal materials, secondary legal materials, to complement the legal materials collected, interviews are conducted with experts or resource persons selected based on the authority exercised by the relevant In this paper, analysis of legal materials is descriptive qualitative, namely identifying primary and secondary legal materials that will be carried out in analyzing problems in a series of processing stages by carrying out an inventory, systematizing, to make it easier to analyze these problems. Based on the analysis, the authors conclude several things, including: (1) the system of proof of criminal procedural law in the process of resolving a case of wrongdoing committed by a doctor still uses the usual burden of proof as stated in article 66 of the criminal procedural code ( KUHAP); (2) providing legal protection to patients under the burden of proof reversed on the settlement of wrongdoing committed by doctors can be seen using: 1. Philosophical Approach, 2. Juridical Approach, 3. Theoretical Approach, and 4. Social Approach.